2010
DOI: 10.1352/1934-9556-48.5.313
|View full text |Cite
|
Sign up to set email alerts
|

Special Education Teachers' Perceptions of Benefits, Barriers, and Components of Community-Based Vocational Instruction

Abstract: This study investigated special education teachers' perceptions of the benefits, barriers, and components of community-based vocational instruction (CBVI). Participants included special education teachers (N   68) from randomly selected high schools in Illinois who had experience delivering vocational curriculum to students with disabilities. Data collection occurred via a survey. Special education teachers perceived CBVI to result in numerous benefits for students with disabilities. Limited resources, require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 38 publications
2
62
1
3
Order By: Relevance
“…Only 40% of special education directors indicated that public transportation was used as a method for transporting students to job sites. Similar to staffing, lack of transportation has been repeatedly identified as a barrier to providing instruction in the community (Baumgart & VanWalleghem, 1986;Dymond, 2012;Kim & Dymond, 2010;Langone et al, 2000;McDonnell, 2010b;Nietupski et al, 1988;Wehman, 2006). Directors reported a range of methods used for transportation, with district vehicles being used by the greatest percentage of respondents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 40% of special education directors indicated that public transportation was used as a method for transporting students to job sites. Similar to staffing, lack of transportation has been repeatedly identified as a barrier to providing instruction in the community (Baumgart & VanWalleghem, 1986;Dymond, 2012;Kim & Dymond, 2010;Langone et al, 2000;McDonnell, 2010b;Nietupski et al, 1988;Wehman, 2006). Directors reported a range of methods used for transportation, with district vehicles being used by the greatest percentage of respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers in this study who came from schools that did not offer CBI cited lack of administrative support as the main reason for why they were not teaching in the community. Kim and Dymond (2010) similarly found that teachers rated lack of administrative support as a barrier to implementing CBVI.…”
mentioning
confidence: 93%
“…A critical step in any vocational training program is to give students with ASD and ID the opportunity to gain experience that will logically lead to jobs after high school in a variety of settings. Although the most directly translatable option would be community-based instruction, many barriers exist that can make it impossible for schools to implement such programs such as funding, transportation, personnel, and location in proximity to possible job placements (Kim & Dymond, 2010). Despite these barriers, the school can offer many realistic, instructional job opportunities.…”
Section: Step 4: Connect the Program To Real-world Experiencesmentioning
confidence: 99%
“…Promoting access to general education classes can provide students with disabilities opportunities to participate in rigorous learning experiences and to develop supportive relationships with their peers (Jackson, Ryndak, & Wehmeyer, 2008/2009). At the same time, many professionals recommend community-based instruction as a strategy for providing relevant learning opportunities that are anchored to everyday community contexts (Kim & Dymond, 2010). How might teachers support youth with significant disabilities as these students participate alongside their peers in educational experiences characterized by both rigor and relevance?…”
mentioning
confidence: 99%